Dry sliding wear behavior of TIG welding clad WC composite coatings - Buytoz, S; Ulutan, M; Yildirim, MM (Elsevier, 2005)
In this study, melted tungsten carbide powders on the surface of AISI 4340 steel was applied by using tungsten inert gas (TIG) method. It was observed that it has been solidified in different microstructures depending on the production parameters. As a result of microstructure examinations, in the surface modified layers an eutectic and dendrite solidification was observed together with WC, W2C phases. In the layer produced, the hardness values varied between 950 and 1200 HV. The minimum mass loss was observed in the sample, which was treated in 1.209 mm/s production rate, 0.5 g/s powder feed rate and 13.9 kJ/cm heat input. (c) 2005 Elsevier B.V All rights reserved.
Keywords: TIG method; surface modification; abrasive wear; dendrite; WC; M7C3